THE RELATIONSHIP BETWEEN ACCOUNTING INFORMATION SYSTEMS AND OPERATIONAL EFFICIENCY IN SMALL AND MEDIUM ENTERPRISES - Rosalina, Rosalina; Suratman, Suratman; Herlianti, Elva; Surahman, Bambang; Kalsum, Ummu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study explores the relationship between Accounting Information Systems (AIS) and operational efficiency in Small and Medium Enterprises (SMEs) through a comprehensive literature review. AIS is increasingly recognized as a crucial tool in helping SMEs improve decision-making processes, streamline operations, and achieve cost efficiencies. For many SMEs, limited resources make the optimization of operational processes essential, and an effective AIS can serve as a strategic asset that enhances data accuracy, supports timely financial reporting, and facilitates effective resource management. This article reviews relevant research from recent studies to evaluate how AIS impacts key performance indicators such as productivity, cost-effectiveness, and overall business efficiency in SMEs. The findings indicate that an efficiently implemented AIS positively correlates with improved operational outcomes by reducing redundancies and fostering real-time data access. Furthermore, the review identifies common challenges faced by SMEs in AIS adoption, including limited technical expertise and budget constraints, and suggests strategies to overcome these obstacles. The study concludes by highlighting the importance of AIS for sustainable growth and providing recommendations for SMEs looking to enhance their operational efficiency through digital transformation.